Systolic array for string matching in NIDS - Thinh, Tran Ngoc; Kittitornkun, Surin (My University, 2007)
In this paper, the rule set of a Network Intrusion Detection System, SNORT [1], is deeply analyzed and a compact encoding method to reduce the memory space for storing the payload content strings of entire rules is proposed. This method can approximately reduce up to 50% of area cost when compared with traditional ASCII coding method. After that, we implement a reconfigurable hardware sub-system for Snort payload matching using systolic design technique. Our system is a processor array architecture that can match strings with throughput up to 3.86 Gbps and area efficient manner.
Keywords: Compact encoding; FPGA; NIDS; String matching; Systolic array